554. Early Clinical Outcomes with Tocilizumab for Covid-19: A Two-Center Retrospective Study. (31st December 2020) - Smoke, Steven; Raja, Karan; Hilden, Patrick; Daniel, Nicole
Abstract: Background: Severe Covid-19 is associated with elevated inflammatory markers, consistent with cytokine release syndrome (CRS). Tocilizumab is an IL-6 inhibitor, effective in treating CRS secondary to CAR-T cell therapy. The efficacy of tocilizumab in treating Covid-19 is unknown. Methods: This was a retrospective cohort study conducted at two hospitals in northern New Jersey. All patients treated with tocilizumab for confirmed or suspected Covid-19 between the dates of 3/10/20 and 4/9/20 at the study sites were included. The primary endpoint was clinical improvement on day 7 after treatment as assessed by respiratory status. Univariate analysis compared data between those who improved and those who did not. Results: Forty five severe and critically ill patients treated with tocilizumab for Covid-19 were evaluated. Eleven (24%), 22 (49%) and 12 (27%) patients improved, had no change and worsened by day 7 after treatment, respectively. Lower WBC and LDH at the time of drug administration as well as shorter time from supplemental oxygen initiation to dose were significantly associated with clinical improvement in the univariate analysis. Conclusion: Tocilizumab administration was associated with a low rate of clinical improvement within 7 days in this cohort of severe and critically ill patients with Covid-19. Disclosures: All Authors : No reported disclosures